ANALISIS DATA SAMPLE MENGGUNAKAN UJI HIPOTESIS PENELITIAN PERBANDINGAN MENGGUNAKAN UJI ANOVA DAN UJI T - Edy Waluyo; Ahmad Septian, Ega Jerilian, Ifnu Nur Hidayat, Muhammad Alfin Prahadi,Teguh Prasetyo, Ade Irpan Sabi (CV. Adiba Aisha Amira, 2024)
Hypothesis Testing: Inferential statistical science includes hypothesis testing, which is used to test statements statistically and draw conclusions as to whether such statements are acceptable or not. The Online Dictionary of Indonesian Language states that a hypothesis is something that is considered true for the reasoning or the ruling of an opinion (proposal, theory, etc.), although its truth needs to be proven. A researcher can perform a hypothetical test to determine whether they accept or reject a hypothesis to get answers to questions. The only way to find out the truth of the hypothesis is to conduct a population survey as a whole. Qualitative library studies, i.e. data collection by studying the theory from relevant literature, are used in this research. This data collection is done by searching and constructing different sources if there is a significant difference in value.